Illumina-based sequencing analysis of pathogenic microorganisms in dental caries patients of different Chinese ethnic groups. Issue 10 (October 2019) - Yun, Chen; Zhiyan, Li; Chong, Zhao; Jing, Liu; Xin, Zhang; Derui, Zhu
Objective: To analyze the pathogenic community diversity of dental caries patients from Tu, Hui, Tibetan, and Han Chinese ethnic groups. Methods: Forty saliva samples were collected from the following patients with dental caries: Tu from Huzhu County (n = 10), Hui from Ping'an County (n = 10), Han from Xining city (n = 10), and Tibetan from Yushu (n = 10). High-throughput sequencing of bacterial 16S rRNA genes (V3-V4) was performed using the Illumina MiSeq sequencing platform. Results: Based on 97% similarity clustering, operational taxonomic units of Tu, Hui, Tibetan, and Han ethnic groups were 181, 210, 38, and 67, respectively. In Tu patients, 11 phyla, 19 classes, and 89 genera were identified, compared with 13 phyla, 21 classes, and 113 genera in Hui patients, two phyla, four classes, and 21 genera in Tibetan patients, five phyla, nine classes, and 34 genera in Han patients, and four phyla, five classes, and 12 genera from the control group. The main pathogens of dental caries included Veillonella, Aggregatibacter, Leptotrichia, Bacteroides, Granulicatella, Streptococcus, and Prevotella . Conclusion: The pathogenic microorganisms of dental caries differ greatly among Tu, Hui, Tibetan, and Han ethnic groups. These findings provide a theoretical basis for the effective prevention and treatment of dental caries in different Chinese populations.